Bayesian analyses of the effect of metacognitive training on social cognition deficits and overconfidence in errors - Köther, Ulf; Pfüller, Ute; Roesch-Ely, Daniela (Journal of experimental psychopathology, 2017)
Social cognition (SC) impairments in schizophrenia predict interpersonal problems and low functional outcome, which might be aggravated by low (meta-) cognitive awareness of individual symptoms and cognitive biases. Metacognitive Training (MCT) aims to raise patients' awareness of cognitive biases, for example overconfidence in errors. We examined whether MCT reduces high-confident false mental state perceptions and tried to identify possible underlying mechanisms of SC impairments. A total of 150 patients were enrolled in a randomized clinical trial comparing the MCT with cognitive remediation (CogPack®) as the active control. Participants were assessed at baseline and at four weeks (post) and further six months (follow-up) later with the Reading the Eyes in the Mind-test also measuring the patients' response confidence. We found that compared to CogPack® MCT reliably reduced the amount of overconfident SC errors by approximately 40% at follow-up. Additionally, we were able to link several symptomatic features and neuropsychological parameters to SC impairments and overconfidence herein.